Organização espacial e questão ambiental: o caso da cidade de Limoeiro do Norte - Ceará - Araújo, Raimundo Lenilde de (2003)
The understanding of the urban area of Limoeiro do Norte and its aspects to the environmental problematic were on a theoritical discussion, haveng as an analytical category the productive agents of that area and the concept of the sustainable cities proposed by the United Nations Conference on Environment and Development which took place in Rio de Janeiro in 1992. The area urban is the result of the action, sometimes contradictory, of the socialagents qho guide the use and occpation of the soil in the city. Having 28.213 inhabitants, according to the 2000 demographic census (56,86 of the total population), the city is considered of medium size in the context of the State of Ceará it is placed in the region of the Low Jaguaribe River and has a differenciate cuttural function due to the Faculty of Philosophy Dom Aureliano Matos (FAFIDAM), which has broad regional perfomance. The initial nucleus started in the XVIIIth century in the context of the settlement of the captainship of Ceará, having as main economic activities the catting, the cotton plantation and the carnauba wax extraction. The country of Limoeiro was setted in 1897 in the separated territory of Russas. The creation of the Diocese in 1938 is considered a landmark in the process of the city development since it has turned out as a regional point for cultural, religious and economic activities in the Low Jaguaribe. After 1960 the State starts the implementation of the graduation courses and the infrastructure linked to the agricultural area through the irrigation projetcts in area. The cuttural function is strengthened through the creation of the Faculty of Philosophy Dom Aureliano Matos in 1968 and the Center of Technological Teaching in 1997. It’s been observed that a city has developed, influenced by the action of set of productive agents of the urban area which was considered outstanding due to the various aspects of the urban evolution process, having the State called attention among them. In relation to the environmental matter not only the need of environment educational programs but also new investments in the social an environmental areas have been pointed out aiming to improve the society/nature relationships in the urban area.